2021
DOI: 10.3390/antibiotics10101150
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Novel Bacteriophages against Escherichia coli Biofilms on Stainless Steel

Abstract: Biofilm formation by E. coli is a serious threat to meat processing plants. Chemical disinfectants often fail to eliminate biofilms; thus, bacteriophages are a promising alternative to solve this problem, since they are widely distributed, environmentally friendly, and nontoxic to humans. In this study, the biofilm formation of 10 E. coli strains isolated from the meat industry and E. coli ATCC BAA-1430 and ATCC 11303 were evaluated. Three strains, isolated from the meat contact surfaces, showed adhesion abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…For instance, phages have been used widely to protect the food chain and livestock against foodborne pathogens including Shiga toxin-producing E. coli [36,37]. Several studies have demonstrated the efficacy of E. coli phage against planktonic and biofilm forms of E. coli [15,38,39]. In another study, an E. coli phage cocktail demonstrating promise for reducing an E. coli infection efficiently without disrupting the gut microbiota in vivo [40].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, phages have been used widely to protect the food chain and livestock against foodborne pathogens including Shiga toxin-producing E. coli [36,37]. Several studies have demonstrated the efficacy of E. coli phage against planktonic and biofilm forms of E. coli [15,38,39]. In another study, an E. coli phage cocktail demonstrating promise for reducing an E. coli infection efficiently without disrupting the gut microbiota in vivo [40].…”
Section: Discussionmentioning
confidence: 99%
“…aureus , P. fluorescens , P. aeruginosa, and L. monocytogenes contribute significantly to food contamination. These bacteria can form biofilms on food contact surfaces, making their eradication difficult and posing a health risk to consumers [ 65 , [97] , [107] , [112] , [118] , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemical methods, for instance, using sanitizers such as chlorine, can make the stainless steel less receptive to biofilm formation, but it can lead to chemical reactions and residue [ 63 , 64 ]. Nowadays, new methods of controlling biofilm on the surface of food industry facilities, such as applying bacteriophages to control biofilm formation, have attracted the attention of researchers [ 65 , 47 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of lytic phages has also been suggested as a method of mitigating E. coli in foods like milk [ 34 , 35 ], beef [ 36 , 37 , 38 ], tomato [ 38 ], broccoli [ 38 ], spinach [ 38 ], lettuce [ 39 , 40 , 41 ], cantaloupes [ 41 ], lamb and mutton [ 42 ], and bivalves [ 43 , 44 ]. However, there are few studies on the use of phages to control E. coli biofilms on different processing surfaces [ 21 , 45 , 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%